Development of Gold Nanoparticle (AuNP)-based Colorimetric Aptasensor for Penicillin G Detection - Darmawati Darmawati; Apon Zaenal Mustopa; Bugi Ratno Budiarto; Siti Irma Rahmawati; Fauzia Nurul Izzati; Rikno Harmoko; Endang Saepudin; Anis H. Mahsunah (Journal of Engineering and Technological Sciences, 2022)
Antibiotics are chemical or biological substances that have the ability to kill pathogens selectively. Currently, high-performance liquid chromatography (HPLC) is used routinely in the detection of antibiotics. However, the cost of analysis and running time are bottlenecks for HPLC to be used for routine tests to detect antibiotics. Alternative methods need to be developed to overcome this issue. In this study, the development of a penicillin G specific biosensor by using a DNA aptamer and gold nanoparticles (AuNPs) was done. Optimal aptasensor conditions were achieved with the concentrations of NaCl and aptamer at 0.25 M and 2 μM, respectively. An aptasensor of this type showed LOD for penicillin G at 3 mg/L and was able to detect penicillin G in the range of 3 to 27 mg/L. The established aptasensor showed specific sensitivity toward penicillin G after testing with several antibiotics, i.e., ampicillin, kanamycin, chloramphenicol, and erythromycin. The aptasensor could detect the presence of penicillin G from culture medium of wild-type, ultraviolet irradiation mutant, gamma irradiation mutant, and ultraviolet irradiation and gamma irradiation mutant strains of P. chrysogenum, at detection concentrations of 9.75 ± 0.004; 25.25 ± 0.005; 37.5 ± 0.005; and 45 ± 0.004 mg/L, respectively.